Spatial and Temporal Variations in Pigment and Species Compositions of Snow Algae on Mt. Tateyama in Toyama Prefecture, Japan - Nakashima, Tomomi; Uetake, Jun; Segawa, Takahiro; Procházková, Lenka; Tsushima, Akane; Takeuchi, Nozomu (Frontiers in Plant Science, 2021)
Snow algae are photosynthetic microbes that inhabit the melting snow surface in alpine and polar regions. We analyzed the pigment and species composition of colored snow collected on Mt. Tateyama in Japan during the melting seasons of 2015 and 2016. High-performance liquid chromatography analyses of the pigments extracted from the colored snow showed that their composition varied within the study area and were classified into four types: Type A (astaxanthin-monoester dominant), Type B (medium astaxanthin-monoester content), Type C (abundant primary carotenoids and free-astaxanthin), and Type D (abundant primary carotenoids and astaxanthin-diesters). Types A and B were most commonly observed in the study area, whereas Types C and D appeared only at specific sites. Analysis of the 18S rRNA gene revealed six major algal phylotypes in the snow, belonging to the Sanguina, Chloromonas, and Chlainomonas groups. The relative abundance of the algal phylotypes showed that Sanguina was dominant (>48%) in both Types A and B, suggesting that the difference in astaxanthin abundance between the two types was caused by the production of pigments in the algal cells. The algal community structures of Types C and D differed from those of Types A and B, indicating that the primary carotenoids and astaxanthin diesters were derived from certain algal species in these types. Therefore, astaxanthin-rich Sanguina algae mostly induced the red snow that appeared widely in this alpine area; however, they were partially dominated by Chloromonas or Chlainomonas algae, causing different pigment compositions.